Degradation and biocompatibility of multistage nanovectors in physiological systems. Issue 10 (16th November 2013) - Martinez, Jonathan O.; Evangelopoulos, Michael; Chiappini, Ciro; Liu, Xuewu; Ferrari, Mauro; Tasciotti, Ennio
Abstract The careful scrutiny of drug delivery systems is essential to evaluate and justify their potential for the clinic. Among the various studies necessary for preclinical testing, the impact of degradation is commonly overlooked. In this article, we investigate the effect of fabrication (porosity and nucleation layer) and environment (buffer and pH) factors on the degradation kinetics of multistage nanovectors (MSV) composed of porous silicon. The degradation by‐products of MSV were exposed to endothelial cells and analyzed for detrimental effects on cellular internalization, architecture, proliferation, and cell cycle. Increases in porosity resulted in accelerated degradation exhibiting smaller‐sized particles at comparable times. Removal of the nucleation layer (thin layer of small pores formed during the initial steps of etching) triggered a premature collapse of the entire central porous region of MSV. Variations in buffers prompted a faster degradation rate yielding smaller MSV within faster time frames, whereas increases in pH stimulated erosion of MSV and thus faster degradation. In addition, exposure to these degradation by‐products provoked negligible impact on the proliferation and cell cycle phases on primary endothelial cells. In this study, we propose methods that lay the foundation for future investigations toward understanding the impact of the degradation of drug delivery platforms. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3540–3549, 2014.